1991
DOI: 10.1159/000108822
|View full text |Cite
|
Sign up to set email alerts
|

Response of Middle Cerebral Artery Volume Flow to Orthostasis

Abstract: Fifteen healthy subjects were tilted at 70° from the horizontal during a period of 4 min while recording the Doppler signal from the middle cerebral artery. Digital signal analysis carried out off-line provided the following data: mean spatial velocity (v), signal power (p) as an index of cross-sectional area, (v•p) as an index of volume flow. Flow as averaged over the entire period of tilted position was found to be 101 ± 25% of the supine steady state. There was evidence for autoregulatory vasodilation inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

1991
1991
2000
2000

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
3
Order By: Relevance
“…Head upright tilt has been claimed to induce dilatation of the middle cerebral artery,19 but such calibre changes have been shown to be negligible,20 and thus allow reliable interpretation of TCD data during head up tilt.…”
Section: Methodsmentioning
confidence: 99%
“…Head upright tilt has been claimed to induce dilatation of the middle cerebral artery,19 but such calibre changes have been shown to be negligible,20 and thus allow reliable interpretation of TCD data during head up tilt.…”
Section: Methodsmentioning
confidence: 99%
“…The common carotid artery diameter of adults decreases as a result of standing [20]. To our knowledge no physiological mechanism or experimental evidence exists for an increase of the diameter of the MCA in orthostasis.…”
Section: Discussionmentioning
confidence: 89%
“…Currently, the transcranial Doppler method is extensively used to measure MCA velocities during BP changes (Aaslid et al 1991), postural changes (Grubb et al 1991;MuÈ ller et al 1991;Frey et al 1993;Savin et al 1995), dynamic exercise and muscle ischaemia (Jùrgensen et al 1992a) and was previously demonstrated as being useful in quantifying cerebral autoregulation (Aaslid et al 1989). The Doppler method allows for cerebral¯ow modi®-cations (Madsen et al 1993) and indicates resistance changes (Jùrgensen et al 1992b;Bailliart et al 1993) but does not permit blood¯ow calculation, since the MCA diameter is not measurable.…”
Section: Discussionmentioning
confidence: 99%